Clinical Oral Health Recommended Care and Oral Health Self-Report, NHANES, 2013-2014 - R. Constance Wiener; Nilanjana Dwibedi; Chan Shen; Patricia A. Findley; Usha Sambamoorthi (Advances in Public Health)
Purpose. The purpose of this study was to determine the concordance of self-reported responses to oral health questions versus clinically evaluated recommended need for oral healthcare by calibrated dentists to determine usefulness of the questions for epidemiological studies. We additionally examined other factors associated with concordant self-reports versus clinical evaluations. Materials and Methods. We used a cross-sectional study design with 4,205 participants, ages 30 years and above, who had complete oral health self-perception data and dental referral data in the NHANES 2013-14. Calibrated dentists completed clinical oral healthcare assessments. The assessments were dichotomized to (1) recommendation for immediate care and (2) routine oral health care. Self-reported oral health needs were measured with 6 items (an overall oral health self-perception question, oral pain within the previous year, impact on job/school, suspected periodontal disease, tooth appearance, and tooth mobility). The key item of interest was the overall oral health self-perception question. Results. Concordance with clinically evaluated recommended need for oral healthcare varied from 52.0% (oral pain) to 65.4% (overall oral health self-perception). Many subgroup differences were observed. Conclusions. The overall self-perception of oral health and the clinical evaluation of oral healthcare need were substantially concordant; other self-reported measures were moderately concordant. This is useful information and points to the need for a minimum set of measures that can provide actionable information and capture the need for clinical dental care.